2021
DOI: 10.3390/coatings11101234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coarse Recycled Aggregate on Failure Strength for Asphalt Mixture Using Experimental and DEM Method

Abstract: Coarse aggregate is the major part of asphalt mixture, and plays an essential role in mechanical performance of pavement structure. However, the use of poor-quality coarse recycled aggregate (CRA) reduces the strength and stability of the aggregate skeleton. It is a challenge to predict accurately the influence of CRA on the performance of asphalt mixture. In this study, both a uniaxial compression test and a direct tensile test were carried out to evaluate the failure strength of asphalt concrete with four CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, the fatigue performance of PC is affected by the interlocking effect of the aggregate structure and the interfacial properties [ 41 ]. Through experiments and numerical analysis [ 37 ], Yao, et al [ 42 ] found that the shape characteristics of aggregate are related to the stress dependence of deformation behavior. The univariate predictor variables of coefficient K 2 were screened using the Bootstrap Forest model in Figure 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the fatigue performance of PC is affected by the interlocking effect of the aggregate structure and the interfacial properties [ 41 ]. Through experiments and numerical analysis [ 37 ], Yao, et al [ 42 ] found that the shape characteristics of aggregate are related to the stress dependence of deformation behavior. The univariate predictor variables of coefficient K 2 were screened using the Bootstrap Forest model in Figure 7 .…”
Section: Resultsmentioning
confidence: 99%
“…[14] Similarly, Yao et al applied the DEM to simulate asphalt concrete specimens and developed a corresponding model to predict the failure strength of the asphalt mixture. [15] Ge et al employed the DEM to investigate the mechanical properties of asphalt mixture at the particle level and demonstrated its ability to accurately analyze related particles. [16] Thus, the DEM is widely utilized in asphalt mixture research, with proven efficacy in particle analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The test results show that optimizing the particle gradation of the aggregate can comprehensively improve the performance of RAC, which can effectively improve its hardening density, compressive strength, and splitting tensile strength, thus improving its durability. In summary, a large number of research results [18][19][20][21] show that particle gradation has an important effect on the performance of various building materials. Good particle gradation can effectively improve the mechanical properties of materials, and improve their permeability and durability.…”
Section: Introductionmentioning
confidence: 99%